Toward a Better Understanding of the Relationship between Belief in the Paranormal and Statistical Bias: The Potential Role of Schizotypy - Dagnall, Neil; Denovan, Andrew; Drinkwater, Kenneth; Parker, Andrew; Clough, Peter (Frontiers in Psychology, 2016)
The present paper examined relationships between schizotypy (measured by the Oxford-Liverpool Inventory of Feelings and Experience; O-LIFE scale brief), belief in the paranormal (assessed via the Revised Paranormal Belief Scale; RPBS) and proneness to statistical bias (i.e., perception of randomness and susceptibility to conjunction fallacy). Participants were 254 volunteers recruited via convenience sampling. Probabilistic reasoning problems appeared framed within both standard and paranormal contexts. Analysis revealed positive correlations between the Unusual Experience subscale of O-LIFE and paranormal belief measures (RPBS full scale, traditional paranormal beliefs and new age philosophy). Performance on standard problems correlated negatively with Unusual Experience and belief in the paranormal (particularly the traditional paranormal belief dimension of the RPBS). Consideration of specific problem types revealed that perception of randomness associated more strongly with belief in the paranormal than conjunction; both problem types related similarly to Unusual Experience. Structural equation modelling specified that belief in the paranormal mediated the indirect relationship between Unusual Experience and statistical bias. For problems presented in a paranormal context a framing effect occurred. Whilst Unusual Experience correlated positively with conjunction proneness (controlling for perception of randomness), there was no association between Unusual Experience and perception of randomness (controlling for conjunction).